The Next Generation Africa Climate Business Plan : Ramping Up Development-Centered Climate Action - World Bank (World Bank, Washington, DC, 2020)
Economic growth and shared prosperity in Sub-Saharan Africa will be increasingly undermined if vulnerabilities to climate change are not addressed. Climate impacts, which are already being felt will escalate significantly, as early as 2030, causing many low-capacity countries to be even more vulnerable. Given the climate sensitivities of multiple engines of growth, agriculture, natural capital, and infrastructure, the urgency for countries to ramp up climate-smart development at scale and across the growth spectrum is an imperative. The Next Generation Africa Climate Business Plan provides a platform to further galvanize climate action by prioritizing its focus on the region’s core development challenges and priorities. The plan is grounded in the World Bank’s commitment to support climate-resilient and low carbon development across the developing world and its solid engagement in technical and financial assistance to support climate action in Africa.